An attempt to determine early and late spontaneous restitution after endurance effort in a man in his sixties based on selected blood indicators. A case study - Mrozkowiak, Mirosław; Sokołowski, Marek (Journal of Education, Health and Sport, 2016)
Mrozkowiak Mirosław, Sokołowski Marek. An attempt to determine early and late spontaneous restitution after endurance effort in a man in his sixties based on selected blood indicators. A case study. Journal of Education, Health and Sport. 2016;6(5):211-235. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.51454 http://ojs.ukw.edu.pl/index.php/johs/article/view/3521 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 14.05.2016. An attempt to determine early and late spontaneous restitution after endurance effort in a man in his sixties based on selected blood indicators. A case study 1Mirosław Mrozkowiak, 2Marek Sokołowski 1Bioergonsport, Nowa Biała 8p, 09-411 Biała 2Akademia Wychowania Fizycznego, ul. Królowej Jadwigi 27/39, Poznań Key words: endurance effort, early and late spontaneous restitution. Autor: dr Mirosław Mrozkowiak1, dr Marek Sokołowski2 1Bioergonsport, Nowa Biała 8p, 09-411 Biała 2Akademia Wychowania Fizycznego, ul. Królowej Jadwigi 27/39, Poznań Summary Introduction. Rest, in its physiological understanding, is a dynamically changeable state which immediately follows the end of physical or mental exercise, or a decrease in their intensity. In such a state, assimilatory processes dominate over dissimilatory processes. Also metabolic by-products are being erased and there occurs the normalization of various bodily processes. What is equally important is the time period after which one finds oneself in an optimal state to undertake the next physical effort – the time of early and late restitution – understood here as physiological restoration of individual rest homeostasis after physical effort without the use of any means enhancing this natural process. The aim of the study is to determine, based on selected blood indicators, the time occurrence of the early and late spontaneous restitution after endurance effort in a man in his sixties. Material and methods. The studied individual who lives a healthy life-style subjected himself to the markings of some selected blood indicators after endurance effort during the process of spontaneous restitution: HCT, MCHC, MCH, PLT, MCV, MPV, PCT, RDW, PDW, pH. Results. Positive results were observed in most of the measured blood features. However, their configuration during 5-day measurement cycle varied. The most positive changes occurred in the following features: HCT percentage, MCH, MCHC, RDW, pH. Conclusion. (1) The process of early and late restitution after endurance effort in a 61year-old man runs accordingly to the generally accepted time intervals. The period of early restitution lasts 3-4 hours, and then the next 41 hours. (2) In order to more accurately determine time periods of the early and late restitution the research on a relatively larger population of varied sex and age is required; such a research would have to be conducted both before and after the physical efforts and it would have to engage various motoric functions of the studied individuals.